2023
DOI: 10.3390/healthcare11050749
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Quality of Life: An Assessment of the Mediating Effect of Social Capital

Abstract: Socioeconomic status has been found to be a significant predictor of quality of life, with individuals of higher socioeconomic status reporting better quality of life. However, social capital may play a mediating role in this relationship. This study highlights the need for further research on the role of social capital in the relationship between socioeconomic status and quality of life, and the potential implications for policies aimed at reducing health and social inequalities. The study used a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…In addition, gender differences emerged as a significant determinant, with females having a higher incidence of mental health symptoms than males. This result is consistent with Thapa et al (2020) and Ma et al (2021) , who found higher rates of mental health symptoms among adult females ( Nutakor et al, 2023a , b , c ). Understanding these gender differences is essential for tailoring mental health interventions and support services to meet the unique requirements and challenges faced by women.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, gender differences emerged as a significant determinant, with females having a higher incidence of mental health symptoms than males. This result is consistent with Thapa et al (2020) and Ma et al (2021) , who found higher rates of mental health symptoms among adult females ( Nutakor et al, 2023a , b , c ). Understanding these gender differences is essential for tailoring mental health interventions and support services to meet the unique requirements and challenges faced by women.…”
Section: Discussionsupporting
confidence: 91%
“…Despite these strengths, the study has limitations that must be considered. First, because the data are cross-sectional, it is not easy to establish causal relationships ( Nutakor et al, 2023a , b , c ). Longitudinal studies would help investigate the temporal relationships between the indicated factors and mental health symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these findings are not consistent across all age groups; e.g., a systematic review revealed no differences in QOL domains between the pediatric population with T1DM and healthy controls [28]. The literature consistently identifies sociodemographic determinants such as female gender, rural environment, lower income, lower education level, and lifestyle choices such as physical inactivity and smoking to be associated with poorer HRQOL in both diabetes types [29][30][31][32][33][34][35][36]. The recommended lifestyle adjustments and complex pharmacological treatment schemes for diabetic patients may affect their QOL from the outset.…”
Section: Introductionmentioning
confidence: 99%
“…6 Studies indicate that SES is the most important determinant of QOL. 7 , 8 Nutakor et al 9 show that SES is a significant predictor of QOL. Abdollahpour et al 10 showed that, among other factors, high SES consistently is the strongest predictor of SRH, promoting economic development can have profound effects on the health of the adult population, especially, improvement in adult SES versus adolescent SES further promotes SRH.…”
Section: Introductionmentioning
confidence: 99%